ketepatan waktu vaksinasi campak sebagai faktor preventif kejadian campak di Kota Yogyakarta - Anggraeni Budi Lestari; Mei Neni Sitaresmi; Tunjung Wibowo (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Timely measles vaccination as a preventive factor on measles occurrence in YogyakartaPurposeThis study aimed to see the relation of timely measles vaccination on measles occurrence.MethodsThis research was a matched case control study. A total of 33 cases and 33 controls were used as samples. Case subjects were toddlers aged 9-48 months with measles clinical symptoms (fever, rash and one of cough, cold/runny or conjunctivitis) who were diagnosed by clinic doctors and confirmed by laboratory (positive IgM) and children without measles (healthy) in the same period who came from the neighboring areas in the city of Yogyakarta as controls.ResultsBivariable analysis showed a significant correlation between timely measles vaccination with occurrence of measles disease where p = 0.0042 and OR = 7 (95% CI: 1.60-63.45). On multivariate analysis, after controlling by including gender and maternal education gained correlation between measles vaccination views of the value of p = 0.008, OR-8.2 (95% CI: 1.7-40.3), gender OR = 0.95 (95% CI = 0.3-2.7 ) and maternal education OR = 1.96 (95% CI = 0.4-9.5).ConclusionThere was a correlation between timely measles vaccination with the occurrence of the disease of measles in the city of Yogyakarta.